2018
DOI: 10.47459/cndcgs.2018.13
|View full text |Cite
|
Sign up to set email alerts
|

Small EU Initiatives in the Process of Pooling and Sharing of Military Capabilities

Abstract: The defense budgets of the Member States of the European Union are rising due to the current economic situation and change in the level of security. The goal of approaching two percent of gross domestic product will probably be reached within one decade. However, the positive trend in the development of the defense budget will not allow small states to acquire the exact numbers of military techniques in the numbers that imply a continuous increase the capacity of national armies.Pooling and sharing is one of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 3 publications
0
2
0
Order By: Relevance
“…Empirical research by Korecki (2018) and Robert et al (2008) examined the logistics graduates' needs in the final year and found that knowledge and cognitive skills can be enhanced through evaluation tests. The study also recommended that a logistics internship is a critical component in HEIs curriculum to enhance ICT knowledge and skills for graduates.…”
Section: Graduates' Knowledge and Cognitive Skillsmentioning
confidence: 99%
See 1 more Smart Citation
“…Empirical research by Korecki (2018) and Robert et al (2008) examined the logistics graduates' needs in the final year and found that knowledge and cognitive skills can be enhanced through evaluation tests. The study also recommended that a logistics internship is a critical component in HEIs curriculum to enhance ICT knowledge and skills for graduates.…”
Section: Graduates' Knowledge and Cognitive Skillsmentioning
confidence: 99%
“…Empirical research by Korecki (2018) and Robert et al. (2008) examined the logistics graduates' needs in the final year and found that knowledge and cognitive skills can be enhanced through evaluation tests.…”
Section: Literature Reviewmentioning
confidence: 99%